Nexus among Democracy, Human Resource Development, and Income Inequality: Three Stage Least Square Estimation for 47 Developing Economies - Ahmad, Tusawar Iftikhar; Rehman, Abdul; Mehmood, Abid; Sattar, Nosheena (iRASD Journal of Economics, 2022)
The purpose behind conducting this study was to examine the relationship among democracy, human resource development and income inequality in developing countries. For this, the study specified three econometric models. The study used panel data for the period 1995 to 2016. First, we have checked the stationarity of variables through Levin, Lin chu (LLC) and IPS test. We used three stage least square (3SLS) for our analysis. Results of model 1 found that income inequality, corruption, and the population had a negative effect on democracy, while human resource development and GDP per capita have a positive effect. In Model-II, income inequality, unemployment and inflation had a negative effect on human resource development, while foreign direct investment, remittances, and democracy had a positive effect. In Model-III results found that human resource development, democracy, GDP per capita and corruption were related negatively to income inequality, while inflation was positively related to income inequality.